The Role of Social Media Marketing Communication on the Instagram Platform in Growing Consumer Buying Intention - Aqila Sofwatun Sabila; Albari Albari (Profesional Muda Cendekia Publishing, 2023)
Today, technological advancements have resulted in a major transformation in the means of communication between consumers and companies. Such developments have also impacted communication through social media, which is a more efficient way to find new consumers and retain existing ones. Therefore, conducting research that relates the purchase intention generated by the variables of Firm-created social media communication (FCSMC), User-generated social media communication (UGSMC), and consumer love for the brand can be useful for predicting consumers' actual purchase of the brand. This study will involve Instagram users in Indonesia who access them at least three times a week. The sample size was determined to be 200 people, selected using the convenience sampling method. The research data is obtained primarily and collected using a questionnaire. Furthermore, the data obtained were analyzed using the SEM approach and the help of the AMOS 22 data processing program. The results showed the importance of the relationship between FCSMC and UGSMC in shaping brand passion and consumer purchase intention. This means that to be able to generate brand passion and consumer buying interest, it is not enough for companies to carry out marketing communications through social media managed by the company; these communications must be able to inspire and shape marketing communications created and disseminated by social media users through their content.